Reproductive concerns and fear of cancer recurrence: a qualitative study of women's experiences of the perinatal period after cancer - Ruth Naomi Vanstone; Karen Fergus; Noor Niyar N. Ladhani; Ellen Warner (BMC, 2021)
Abstract Background Young female cancer survivors are at a disproportionate risk of suffering significant psychological distress following treatment, particularly fears of cancer recurrence (FCR). While previous research has established the robust relationship between FCR and family matters (e.g., family planning and motherhood), there is a paucity of information about how a history of cancer affects women's psychological functioning throughout the perinatal period. The present investigation sought to better understand women's experiences of pregnancy and the postpartum period following cancer treatment through a qualitative analysis. Methods Ten women participated in a semi-structured, one-on-one interview either over telephone or video conferencing (Zoom). Women were recruited from Sunnybrook Health Sciences Centre in Toronto, as well as through online cancer support platforms, and social media sites. Participants all had a past cancer diagnosis; no active disease; were 45-years of age or younger; currently in the perinatal period; and spoke English fluently. The study employed a grounded theory analysis by which verbatim interview data were analysed using a constant comparison method until data saturation was reached. Results The qualitative analysis yielded I'm So Happy, But Also Terrified, as the core category, indicative of the duality of emotional experience that characterized the perinatal period for these women. Additionally, four higher-order categories emerged revealing how women go through a process of grief related to potential fertility loss; conditional joy during and after pregnancy due to the lingering weight of cancer; frustration with a lack of resources regarding perinatal health after cancer; and hope as they enter into motherhood. Conclusion These results suggest that women in the perinatal period with a history of cancer may be at an increased risk for psychological distress and require additional fertility and reproductive resources both during and after cancer treatment. This research is an important step in further understanding women's experiences of pregnancy after cancer and may help to inform future research and healthcare practices, in addition to improving perinatal care after cancer.